PEMBELAJARAN LARI CEPAT MELALUI PERMAINAN BENTENGAN UNTUK MENINGKATKAN PARTISIPASI DALAM PEMBELAJARAN PENJASORKES PADA SISWA KELAS III SD NEGERI 2 RANDUBLATUNG KABUPATEN BLORA 2013/2014 (Department of Physical Education, Sport, Health and Recreation, 2015)
The goal of this research is to enhance students’ enthusiasm and participation in learning basic sprint for 3rd grade Sport subject at SD Negeri 2 Randublatung Blora year 2013/2014 through traditional Bentengan Game. The research method used is collaborative class action research. The research result shows how surprisingly traditional game is really suitable to stimulate students’ enthusiasm of learning. The graph shows significant enhancement from the firs cycle which only has 69,69% of success rate to 93,90% of success rate in the end of second cycle. This result follows the surveys that show most of students feels certain excitement along with this learning method. It concludes that learning basics sprint through traditional bentengan game able to enhance students’ enthusiasm and participation.